Molecular identification and amylolytic potential of a thermophilic bacteria species from refuse dump in Ile-Ife, Nigeria - Omoboye, Olumide; Bakare, Mufutau; Adewale, Isaac; Oyedeji, Olaoluwa (International Journal of Biological Research, 2014)
Molecular identification and amylolytic potential of a thermophilic bacterium species isolated from refuse dump was investigated. Bacterial isolates were identified by morphological and biochemical characterization while amylolytic bacterium of interest was identified by molecular analysis using 16S rRNA gene sequencing. The bacterium with the highest ?-amylase activity was selected for enzyme production. The optimal conditions for ?-amylase secretion were determined by varying the pH, temperature, percentage soluble starch, nitrogen sources and carbon sources. The isolated and identified bacteria were Bacillus alvei (40%) Bacillus licheniformis (40%) and Bacillus brevis (20%) while Bacillus licheniformis RD24 was identified by 16S rRNA gene sequencing. The peak of amylase production was at 20 h of incubation (925 µg/ml/min). The optimum pH and temperature for the enzyme production were 7 and 45oC respectively. Enzyme production medium with 1% starch gave highest enzyme activity of 102 ± 5.3 µg/ml/min. Peptone gave an enzyme activity of 165 ± 8.97 µg/ml/min and yeast extract gave 52.26 ± 2.86 µg/ml/min. Of the raw starches, cassava flour gave the highest specific activity of 72 ± 0.07 Units/mg proteins, while sorghum starch gave the lowest specific activity of 5 ± 1.52 Units/mg proteins. The study concluded that starch-rich household waste can be employed for amylase production using Bacillus licheniformis RD24. Keywords: Alpha Amylase, Bacillus Species, Optimum, Soluble Starch, Thermophilic.